2017
DOI: 10.1021/acs.jmedchem.7b00338
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Fluorescent Tracer for the Free Fatty Acid Receptor 2 (FFA2/GPR43)

Abstract: The free fatty acid receptor 2 (FFA2/GPR43) is considered a potential target for treatment of metabolic and inflammatory diseases. Here we describe the development of the first fluorescent tracer for FFA2 intended as a tool for assessment of thermodynamic and kinetic binding parameters of unlabeled ligands. Starting with a known azetidine FFA2 antagonist, we used a carboxylic acid moiety known not to be critical for receptor interaction as attachment point for a nitrobenzoxadiazole (NBD) fluorophore. This led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
1
36
1
Order By: Relevance
“…It was found that both unlabelled ligand displayed similar k off rates but different k on rates which is reflected in their affinity at equilibrium. The NanoBRET assay has also recently been used to resolve the kinetics of unlabelled ligands at the free fatty acid receptor 2 in cell membranes 58 . The ability to also perform these measurements in whole cells opens up the potential to assess the effect of cellular environments on rate constants as it has been shown that for some receptors that an intact cell environment can alter the binding kinetics 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both unlabelled ligand displayed similar k off rates but different k on rates which is reflected in their affinity at equilibrium. The NanoBRET assay has also recently been used to resolve the kinetics of unlabelled ligands at the free fatty acid receptor 2 in cell membranes 58 . The ability to also perform these measurements in whole cells opens up the potential to assess the effect of cellular environments on rate constants as it has been shown that for some receptors that an intact cell environment can alter the binding kinetics 59 .…”
Section: Discussionmentioning
confidence: 99%
“…However, bound fluorescent agonists may induce receptor internalization during the course of a binding experiment on intact cells, which may result in the observation of lower pK i values for unlabeled ligands as compared with binding assays on cell homogenates (Cheng and Prusoff, 1973;Guo et al, 2010). The NanoBRET-based binding assay can detect binding of a fluorescent ligand to living cells expressing the Nluc-tagged receptor of interest with a high resolution in time, which also allows for the measurement of a full association-binding curve from a single sample (Hansen et al, 2017;Stoddart et al, 2018). Detection of the association binding of a fluorescent probe in the presence of unlabeled ligands allows quantification of the kinetic rate constants and K D (5 k off /k on ) values of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Human wild type and mutant FFA2 receptors with NanoLuc Luciferase fused to their N terminus were cloned into the pcDNA5/FRT/TO expression vector as described previously 37 and used to generate doxycyline-inducible Flp-In T-REx HEK293 cell lines. For assays based on transient transfection a pcDNA5/FRT/TO vector expressing receptors fused to an HA-tag at their C terminus was cloned as previously described 38 .…”
Section: Methodsmentioning
confidence: 99%